ANALISIS STRATIGRAFI DAN IDENTIFIKASI FASIES SEISMIK PADA INTERVAL BARENG LISU, DAERAH KOTAGARO, CEKUNGAN SUMATRA TENGAH - Vebryatna, Vicco Oryzavica; Noeradi, Dardji (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2019)
The Kotagaro area is one of the hydrocarbon field in the Central Sumatra basin one of the old giant hydrocarbon basins in Indonesia. Only Post-rift deposit are well explored in the Kotagaro are,while Synrift deposit of Pematang Group still not being explored as a reservoir, because they are not a focus in the development study. Research on synrift interval is expected to be new knowledge, especially in the Kotagaro area. This study aims to explore (new insights) regarding synrift interval by analyzing seismic facies and interpreting the depositional environments of the study area. This study used 2D and 3D seismic data and data from a well located outside the study area. Well data is used for well-seismic tie. The methods used in this study included well-seismic tie, 2D and 3D seismic interpretations the synrift intervals, generation of time structure maps and isochrones maps seismic facies analysis, and interpretation of depositional environments. Based on this analysis, the research area has four seismic facies, Chaotic Wedge (AM), Divergent Wedge (DM), Hummocky Wedge (HM), and Parallel Wedge (PM). The four seismic facies showed that the study area was deposited in the fluvial zone, alluvial fan zone, deep lacustrine zone, shallow lacustrine zone, and lacustrine shoreline zone.